Gerioperative nursing care : principles and practices of surgical care for the older adult - Shippee-Rice, Raelene V. (Springer, 2012)
This timely volume introduces gerioperative care, a new model of surgical care for the elderly designed to improve surgical outcomes and prevent complications through a focus on communication and relationship-centered care. It is the only book to specifically address the care of older adults undergoing surgery, providing practitioners with critical, practical, and theoretical information from the initial decision to have surgery through the first follow-up visit post-discharge. The text includes the anatomy and physiology of aging, preoperative care, intraoperative and post-anesthesia care, po.